Customization Of Requirements Modeling Tool For Software Engineering Education - Subhiyakto, Egia Rosi (2014)
In the developing a software, there is a part of modeling the requirements. Modeling the requirements usefully to communicate all stakeholders and as a blueprint. There are modeling tools used to model the requirements such as Rational Rose, Enterprise Architect, Magic Draw, StarUML, ArgoUML, UML Designer, etc. Modeling tools that available gets more complicated to use and when compared majority tools more emphasis on modeling for industrial rather than education. In this study perform the customization tool for software engineering education and evaluate effectiveness the custom tool. The research methodology in this study is questionnaire, interview and literature review related with the study. The custom tool focus only on use case diagram including use case elements and use case description. Development the system start with elicited the requirements of the system, hardware requirements, and software requirements. The testing stage performed to get evaluation from the system developed. In the testing performed test the functional of the system. Evaluation obtained that the system usefulness, easy to use, and easy to learning. Besides, software engineering students are involved satisfied with the system.